ANALYSIS OF LOCUTIONARY, ILLOCUTIONARY, AND PERLOCUTIONARY SPEECH ACTS IN GREENFIELDS ADVERTISEMENT: THE ANSWER TO THE SEARCH FOR THE BEST MILK FOR FAMILIES - Febriyana, Mutia; Ray, Sukma Adelina (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2026)
The purpose of this study is to characterize and explain the locutionary, illocutionary, and perlocutionary speech acts seen in the Greenfields video advertisement: Answers to the Search for the Best Milk for Families. Advertising language is a persuasive communication tool that influences consumer attitudes and behaviors in addition to providing information. J.L. Austin's pragmatic theory serves as the basis for this study's descriptive qualitative methodology. Transcripts of advertising stories and conversations served as data sources. Listening and note-taking methods were used as data collection strategies. The findings of the study indicate that: (1) Declarative sentences that accurately describe the product's benefits dominate the locutionary speech acts; (2) The most common illocutionary speech acts are directives (subtly inviting) and assertives (stating, emphasizing), which serve to create a premium brand image; (3) Audiences are encouraged to choose Greenfields products as a family nutrition solution by eliciting a sense of security and trust. The conclusion of this study suggests that the effectiveness of advertising messages depends on a combination of precise and literal information and the strength of the purpose (illocutionary force), which appeals to customers' emotions.